Methodological performance of selenium determination in ruminal fluid by hydride generation atomic absorption spectroscopy - Brambilla, Emilio Cesar; Cseh, Susana Beatriz; Fernandez, Eduardo Luján; San Martino, Silvina (Ediciones INTA, 2021)
Selenium (Se) is a trace element used by multiple enzymes. In ruminants, Se present in food is released to ruminal fluid allowing its absorption in the small intestine. Se release may be analysed by hydride generation atomic absorption spectroscopy (HG-AAS). According to the Association Official of Analytical Chemists (AOAC), analysing the methodological performances is important to support the results of a methodology. The aim of this study was to develop and verify the analytical methodology of Se determination in ruminal fluid by HG-AAS. According to the AOAC guide, the parameters to be analyzed, and their respective acceptance criteria (AC) are: applicable range (AC: 0.220 - 9.68 µg/l), bias (AC: 70-125%), precision by repeatability (RSDr%) (AC: < 21%), intermediate precision (RSDip%) (AC: < 21%), recovery (AC: 80-110%), limit of detection (LOD) (AC: < 0.22 µg/l), and relative uncertainty (AC: <15%). The technique used is based on a wet digestion of ruminal fluid with HClO4 , H2 SO4 and HNO3 concentrated at temperatures ranging from 120°C to 180°C. Then the digest was pre-reduced in HCl at 50 % and was quantified in the HG-AAS. The results obtained were: LOD 0.196 µg/l, bias 96.8% (1.25 µg/l); 98.3% (2.50 µg/l); 94.8% (5.00 µg/l), precision by repeatability 8.61% (3.28 µg/l); 8.90 % (3.52 µg/l); 9.80% (1.85 µg/l), intermediate precision RDSip 10.2%, recovery 109.2% (10 µg/l); 96.7% (25 µg/l); 96.8% (50 µg/l) and applicable range 0.196-62.5 µg/l. The values obtained are within the requirements stated by the AC.